Implementing the INTER-SETS Learning Model in Acid–Base Chemistry to Improve Students' Science Process Skills and Scientific Attitudes - Feri Andi Syuhada; Eli Rohaeti; Hari Sutrisno; Sakinah Zubair (Postgraduate, University of Mataram, 2026)
This study examined whether students’ science process skills (SP) and scientific attitudes (SA) changed following the implementation of the INTER-SETS learning model in acid–base chemistry. A pre-experimental one-group pretest–posttest design involving 34 senior high school students was employed. Science process skills were measured using an essay test, whereas scientific attitudes were assessed using a validated questionnaire. Data were analyzed using one-sample Hotelling’s T² based on difference scores (posttest–pretest), followed by univariate analyses at a significance level of 0.05. The results revealed statistically significant simultaneous improvements in SP and SA after implementing the INTER-SETS learning model (Hotelling’s Trace = 11.37, F(2, 28) = 159.24, p < 0.001). Follow-up analyses also showed significant improvements in science process skills (F(1, 29) = 197.42, p < 0.001) and scientific attitudes (F(1, 29) = 57.80, p < 0.001). These findings suggest that integrating guided inquiry with Science, Environment, Technology, and Society (SETS) contexts provides meaningful learning experiences associated with improvements in students’ scientific competencies and attitudes during acid–based learning. However, because this study employed a one-group pretest–posttest design, the findings should be interpreted as evidence of improvement rather than definitive causal effects.